2011
DOI: 10.1177/147323001103900505
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 2 Receptor α Gene Polymorphism and Risk of Multiple Sclerosis: A Meta-Analysis

Abstract: This meta-analysis studied the association between interleukin 2 receptor a (IL2RA) gene polymorphisms rs2104286 and rs12722489 and susceptibility to multiple sclerosis (MS). Case-control genetic association studies published before January 2011 were retrieved from the PubMed and EMBASE databases and the Cochrane Library. Eight studies comprising 13 569 patients and 23 435 controls met the selection criteria for metaanalysis of the IL2RA rs2104286 polymorphism. Using a fixed-effects model, the T allele and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
(44 reference statements)
0
10
0
Order By: Relevance
“…A priori power analysis assuming a disease prevalence of 0.001, [1] with a minor allele frequency of 0.25, as observed in Caucasian populations, and the previously described relative risk of 1.25, [8,9] indicated that our series (n=2,808) has a 93% probability of identifying nominally significant differences in genotype frequencies between MS patients and controls. Analysis of MS subgroups, assuming the same parameters, indicated a statistical power of 91% for familial MS, 59% for sporadic MS, 83% for RRMS and 79% for progressive MS (PrMS; PPMS and SPMS).…”
Section: Power Analysismentioning
confidence: 62%
See 4 more Smart Citations
“…A priori power analysis assuming a disease prevalence of 0.001, [1] with a minor allele frequency of 0.25, as observed in Caucasian populations, and the previously described relative risk of 1.25, [8,9] indicated that our series (n=2,808) has a 93% probability of identifying nominally significant differences in genotype frequencies between MS patients and controls. Analysis of MS subgroups, assuming the same parameters, indicated a statistical power of 91% for familial MS, 59% for sporadic MS, 83% for RRMS and 79% for progressive MS (PrMS; PPMS and SPMS).…”
Section: Power Analysismentioning
confidence: 62%
“…[18,19] The goal of this study is to further define the role of IL2RA rs2104286 and IL7R rs6897932 in the susceptibility to MS. To this end, we characterized these two variants in a case-control series of MS patients from Canada. This cohort is noticeably distinct from those described in most association studies of IL2RA and IL7R with MS, [8,9] as it contains a higher proportion of patients with a family history of disease (82.5%), as well as a higher number of patients presenting PPMS (25%). Interestingly neither variant resulted in a significant association with disease in the entire cohort (Table 1) despite having a 93% power of detection.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations